2014
DOI: 10.1016/j.jpainsymman.2013.06.011
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity of Nurses' Attitudes and Practice of Sedation at the End of Life: A Systematic Literature Review

Abstract: Most nurses administered sedation until death only within the given circumstances because of the anticipatory benefits in controlling refractory symptoms and suffering. Some of them experienced burdens during PS delivery; these could be supported by operational guidelines and task-related training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 41 publications
2
57
0
1
Order By: Relevance
“…Our study confirmed previous studies showing that nurses, who play an important role in sedation, appear to be the group most vulnerable to doubt during sedation [22]. Following the discussion and the medical decision to sedate, they are the ones involved in its “ultimate” implementation: preparation and injection of the medication.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study confirmed previous studies showing that nurses, who play an important role in sedation, appear to be the group most vulnerable to doubt during sedation [22]. Following the discussion and the medical decision to sedate, they are the ones involved in its “ultimate” implementation: preparation and injection of the medication.…”
Section: Discussionsupporting
confidence: 88%
“…Teamwork helps reduce individual distress by clarifying the course of action, providing an opportunity for dialogue and organisation and offering professional recognition and support [48]. In addition to extending psychological support to health care providers [22], teamwork enables providers to build cooperation and devise ways to arrive at agreed rules governing their work. Teamwork thereby makes it possible for providers to reconfigure their approach to their professional competence in the sedation situations that constitute a burden for them [49].…”
Section: Discussionmentioning
confidence: 99%
“…As noted in the findings, the challenge of providing pain relief without unwanted side-effects remains a dilemma, 69 especially if patient dignity is to be preserved.…”
Section: Symptom Controlmentioning
confidence: 97%
“…The authors identified inconsistencies and a lack of clarity on what constituted "intolerable" or "refractory" suffering and proposed that the patient's ability to consent should be explicitly recorded, that the team have a shared and explicit understanding of the terminology and definitions of sedation, and that formal mechanisms for support (such as clinical supervision) are offered to staff. The development of guidelines has become a focus and priority due to concerns and uncertainty surrounding decisionmaking dilemmas and the connotations and inferences related to euthanasia and palliative sedation (Abarshi et al, 2014;Schildmann & Schildmann, 2014;Cherny & Radbruch, 2009;Hauser & Walsh, 2009;Legemaate et al, 2007;Verkerk et al, 2007;de Graeff & Dean, 2007;Engström et al, 2006).…”
Section: Introductionmentioning
confidence: 99%